Differentiated Durable Goods Monopoly: A Robust Coase Conjecture - Nava, Francesco; Schiraldi, Pasquale (American Economic Review, 2019)
The paper analyzes a durable goods monopoly problem in which multiple varieties can be sold. A robust Coase conjecture establishes that the market eventually clears, with profits exceeding static optimal market-clearing profits and converging to this lower bound in all stationary equilibria with instantaneous price revisions. Pricing need not be efficient, nor is it minimal (equal to the maximum of marginal cost and minimal value), and can lead to cross-subsidization. Conclusions nest both classical Coasian insights and modern Coasian failures. The option to scrap products does not affect results qualitatively, but delivers a novel motive for selling high cost products. (JEL C78, D42, L12)